Editor’s Note - Rehaut, Lucas (Consilience, 2014)
Dear Readers, It is my sincere pleasure to announce the official publication of Issue XI of Consilience: The Journal of Sustainable Development. Our team has spent the past few months working to gather the diverse and substantial selection of articles you see here today. Consilience celebrated the publication of its tenth issue in May of 2013, and Issue XI represents another strong step forward for the journal, as well as another great contribution to the expanding body of sustainable development research. As per the mission of Consilience, the articles in XI cover a wide array of topics, geographies, and academic disciplines. Fanyuan Lin compares watershed service payment schemes in New York City and Beijing, while Innocent Chirisa discusses the challenge of balancing local needs, costs, and sustainability for urban planning in Zimbabwe. Rachel Tiller considers the effects of expanded salmon aquaculture in Norway, and Giulia Baldinelli’s photo essay shows the ways Bolivians are using conservation as a means of adapting to climate change. The articles of Issue XI concern serious problems. Caroline Harfouche and Diane Jung document their research on the negative effects of anthropogenic activity on freshwater lagoons in the Dominican Republic. Rochanya Generous explains the relationship between bacterial quorum sensing and coral reef health, as well as how it is threatened. Scott Pearse-Smith argues against the use of large dams as a development tool, focusing on the Mekong River Basin as an enlightening case study. In his opinion piece, Ranu Dhillon looks at America’s obesity epidemic through the lens of sustainable development and comes to some interesting conclusions. But there are also solutions. Drs. Mishra and Dash discuss the merits of biofertilizers as a tool for sustainable agricultural development. Hege Westskog and Tanja Winther explore the ways public attitudes about energy use can be integrated into better energy policies. Finally, Subas Dhakal takes us via his photo essay to Perth, Australia, and shows us how activist groups are successfully communicating and implementing sustainability goals in their local domains. Our mission remains to promote dialogue and understanding of issues in sustainable development that affect not only individual communities, but the greater collective well-being of our planet. Our authors have worked diligently to provide innovative perspectives to perpetual challenges in sustainable development. We invite you to think critically about their arguments, further our understanding of their claims, and challenge their assumptions. Through interaction between practitioners, scholars, and researchers, we hope the ensuing dialogue will offer fruitful solutions to the most pressing challenges facing our planet. I invite you to read Issue XI as well as our past publications and Briefings articles. As always, please contact us with any questions, critiques, feedback or submissions at contact@consiliencejournal.org. Regards, Lucas Rehaut Editor-in-Chief Consilience: The Journal of Sustainable Development